The cruelty of heresy an affirmation of Christan orthodoxy - Allison, Christopher FitzSimons, 1927- (Harrisburg, NJ Morehouse, 1994)
Includes bibliographical references and index.
Keywords: Heresies, Christian -- history -- early church, ca. 30-600.